Peningkatan Hasil Belajar IPA Siswa Kelas IV melalui Strategi Belajar Kooperatif Index Card Match - Destiawati, Neng Dewi; Noviana, Sarah; Mirawati, Mirawati; Juhji, Juhji (PGMI IAIN Lhokseumawe, 2024)
This study assesses how the Index Card Match cooperative learning technique affects fourth-grade students' scientific learning results. Thirty students were split into experimental and control groups for this quasi-experimental study, which used a pretest-posttest control group. There were fifteen pretest and posttest questions in all. Science achievement exams were used to gather data before and after the intervention. Paired and independent t-tests were used for analysis. With a significance value of Sig= 0.859 > 0.005, the results demonstrated that the experimental group employing the Index Card Match approach had significantly better learning outcomes than the control group using traditional teaching strategies. These results suggest that the Index Card Match method works well for both raising students' social skills and their comprehension of science ideas. The study concludes that teachers should incorporate the Index Card Match cooperative learning approach into their lesson plans to improve student learning outcomes and educational quality.